Systematic analysis of the pharmacology of myoinositol and D-chiroinositola - T. E. Bogacheva; O. A. Gromova; I. Yu. Torshin (Фармакокинетика и Фармакодинамика)
The article presents an analysis of publications on myoinositol in order to clarify the possibilities of prescribing drugs based on it. Myoinositol is one of the endogenous human metabolites that has a significant effect on the functioning of cells and tissues of the whole body. The main function of myoinositol and its derivatives is to participate in intracellular signal transmission and ensure the functioning of such important receptors as insulin receptors, catecholamines, metabotropic receptors of various neurotransmitters, growth factors, etc. (Myoinositol is the basis for the synthesis of an important group of signaling molecules, inositol phosphates, which mediate signal transmission from growth factor receptors and neurotransmitters). Most inositol-dependent proteins with known functions are necessary for the vital functions of the cardiovascular, immune system, and connective tissue structure. Equally important is the role of myoinositol in maintaining the functioning of the central nervous system (including neurotrophic and neuroprotective roles), sugar metabolism (primarily the signaling cascade of insulin) and the functioning of the kidneys and liver. Myoinositol subsidies contribute to the prevention of folate-resistant malformations and neuroprotection of the brain under stress.